2019
DOI: 10.9734/ajbgmb/2018/v1i430048
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening of Etlingera elatior (Torch Ginger) Cultivated on Different Dosage of Biochar

Abstract: Objective: This study was carried out with an objective to investigate the impact of biochar on phytochemical composition in plant especially Etlingera elatior cultivated on different dosage of biochar. Methods: Etlingera elatior was cultivated on the pot with 20 cm diameter and 35 cm height. 3 replicates for pots of Etlingera elatior was cultivated and label as 0%, 5% and 20%. The ordinary farm soil without biochar (0%) as control, fertilized soil with biochar; 5% and 20%. In a net house and watered twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…On the one hand, it can serve as a fast source of organic matter (23 %WSOC). On the other hand, part of the organic carbon remains in the mass of the biochar and has the potential, due to the activity of living organisms, to slowly pass into the substrate and further into the soil solution, thereby enriching it with available organic matter [14,15]. Thus, the use of corn straw biochar can have a beneficial effect on the nutrition conditions of rhizosphere microorganisms and, as a consequence, plants by improving the properties of the soil substrate.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, it can serve as a fast source of organic matter (23 %WSOC). On the other hand, part of the organic carbon remains in the mass of the biochar and has the potential, due to the activity of living organisms, to slowly pass into the substrate and further into the soil solution, thereby enriching it with available organic matter [14,15]. Thus, the use of corn straw biochar can have a beneficial effect on the nutrition conditions of rhizosphere microorganisms and, as a consequence, plants by improving the properties of the soil substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar had no effect on the phytochemical properties of plantlets. Few studies have reported the benefit of biochar in increasing secondary metabolites in plants (Umaru, Samling, & Umaru, 2018). Researchers generally target plant growth and crop productivity (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%